Rapid Screening of Phenolic Compounds from Wild Lycium ruthenicum Murr. Using Portable near-Infrared (NIR) Spectroscopy Coupled Multivariate Analysis - Arslan, Muhammad; Xiaobo, Zou; Tahir, Haroon Elrasheid; Shi, Jiyong; Zareef, Muhammad; Rakha, Allah; Bilal, Muhammad (Analytical letters, 2021)
This study was designed to quantify the phenolics and flavonoids in wild Lycium ruthenicum Murr. using portable near-infrared (NIR) spectroscopy integrated with chemometric algorithms. Synergy interval partial least squares with ant colony optimization (Si-ACO-PLS) was applied to optimize and capture the target variables for the determination of phenolics and flavonoids. The constructed models were evaluated using the correlation coefficients of the calibration (Rc) and prediction (Rp), the root mean square error of prediction (RMSEP) and the residual predictive deviation (RPD). The Si-ACO-PLS models yielded 0.8522 ≤ Rc ≤ 0.9500, 0.8226 ≤ Rp ≤ 0.9448, 1.43 ≤ RMSEP ≤ 3.77 and 2.09 ≤ RPD ≤ 2.88. Conclusively, portable NIR spectroscopy coupled with Si-ACO-PLS was demonstrated to be simple, rapid and cost-effective to quantify the phenolics and flavonoids in L. ruthenicum samples.